Koomarri. - Koomarri Association A.C.T. (Phillip, ACT : Koomarri)
"Koomarri supports people who live with a disability to achieve their life goals, dreams and aspirations. We support more than 300 people and their families across a diverse range of business, training, community and residential initiatives."--About us.
Title from title screen (viewed on 17 January 2019)
Mode of access: Available Online. Address as at 21/01/2019
Selected for archiving
Keywords: People with disabilities -- Services for -- Australian Capital Territory; People with disabilities -- Australian Capital Territory; Australian